Pairing patterns in polarized unitary Fermi gases above the superfluid transition - Attanasio, Felipe; Rammelmüller, Lukas; Drut, Joaquín E.; Braun, Jens (Physical review, 2022)
We nonperturbatively study pairing in the high-temperature regime of polarized unitary two-component Fermi gases by extracting the pair-momentum distribution and shot-noise correlations. Whereas the pair-momentum distribution allows us to analyze the propagation of pairs composed of one spin-up and one spin-down fermion, shot-noise correlations provide us with a tomographic insight into pairing correlations around the Fermi surfaces associated with the two species. Assuming that the dominant pairing patterns right above the superfluid transition also govern the formation of condensates in the low-temperature regime, our analysis suggests that the superfluid ground state is homogeneous and of the Bardeen-Cooper-Schrieffer type over a wide range of polarizations.
Gesehen am 24.08.2022